ANALISIS MAKNA PERIBAHASA MANDARIN MENGGUNAKAN UNSUR RASA “PAHIIT” - Monice Claura; Lily Thamrin; Bun Yan Khiong (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
Proverb is a word that is often used by people in ancient times until now and is a part of Chinese culture. Proverbs have many elements, namely animals, plants, the human body, numbers, colors, flavors and other elements. Mandarin proverbs are often used by old people in general and become part of their lives. Until now, proverbs are often used in people's lives, both in learning and in daily conversation.However, young people today rarely know about proverbs and use proverbs in their lives. Therefore, the writer chose mandarin proverbs as the object of research. The writer analyzes the meaning of Chinese proverbs using the element of taste, namely the bitter taste element from the Chinese Proverb Dictionary, namely “Xuě Shēng Chéngyǔ Cídiǎn and Hànyǔ chéngyǔ xuéxí cídiǎn ” and the writer collecs 34 proverbs and analyzes the meaning of the 34 proverbs.Through the method of analysis and description, the writer can conclude that among 34 proverbs, 21% of idioms have positive meanings, 12% have negative meanings, and 68% contain meanings from these proverbs.